DRUG UTILIZATION PATTERNS AND COSTS ANALYSIS IN NON SMALL CELL LUNG CANCER PATIENTS AT DR. H. A. ROTINSULU LUNG HOSPITAL BANDUNG - Nurfathonah, Annisa
The high incidence and poor prognosis of non-small cell carcinoma lung cancer (NSCLC), as well as the high cost of treatment, encouraged the need for research on drug use and cost analysis. This study aimed to describe the pattern of anticancer drug use in patients with NSCLC, assess its suitability with current guideline, ensure rational drug use, analyze treatment costs, and identify factors that affected the duration of therapy at the Dr. H. A. Rotinsulu Lung Hospital Bandung. This study was a retrospective cross-sectional study that analyzed secondary data from electronic medical records and BPJS claim data for KPKBSK patients for the period January-December 2023. Demographic data, anticancer drug use, premedication, treatment costs, and factors affecting therapy duration were analyzed. Conventional chemotherapy used consisted of cisplatinpemetrexed (31.7%), carboplatin-paclitaxel (29.0%), and carboplatin-pemetrexed (4.3%). Targeted therapies used were gefitinib (20.4%), erlotinib (7.0%), afatinib (5.4%), and alectinib (2.2%). The selection of first-line anticancer was not in accordance with the guideline because immunotherapy and osimertinib were not included in the national formulary and thus were not available in the hospital. The selection of cisplatin for advanced-stage NSCLC patients who were elderly and had comorbidities was also not in accordance with management recommendations. The selection of furosemide and neurotrophic vitamins as premedication was not in line with scientific recommendations. There were also several major drug-drug interactions between anticancer and other drugs, such as furosemide and cisplatin. In addition, there were several adverse drug reactions potentially caused by anticancer such as nausea, vomiting, diarrhea, allergic dermatitis, electrolyte imbalance, and anemia. The results of the cost minimization analysis found that carboplatinpaclitaxel and erlotinib had the lowest cost. Statistical test results showed that there was a significant difference in the duration of patient therapy between the body mass index categories of patients given conventional chemotherapy (p=0.041). There was also a significant difference in the duration of therapy between the education levels of patients given conventional chemotherapy (p=0.035) and targeted therapy (p=0.022).